Citizen support for the pursuit of gender equality in US foreign policy. Issue 3 (26th May 2020) - Lizotte, Mary-Kate; Eichenberg, Richard C.; Stoll, Richard J.
Abstract: We ask two questions in this article: First, what is the level of public support for the pursuit of gender equality in foreign policy? Second, what are the most significant correlates of that support? We report the results of the first national opinion survey that queried citizens about their support for policies to increase global gender equality. We find that an average of 60 to 90 percent approve of pursuing gender equality and specific programmatic initiatives. Americans also strongly agree with one rationale for pursuing global gender equality: 65 percent agree that "The world would be a more peaceful place if more women were involved in making decisions." Second, we find that a number of individual characteristics and personal values are strongly correlated with support for gender initiatives. Our results also suggest that women's greater endorsement of universalism values explains their higher levels of support for global gender equality.